Analysis of the implementation of the Montessori method in daycare services for children aged 1-3 years - Kristian, Wemni; Wulan, Sri; Dhieni, Nurbiana (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2024)
Background : Daycare centers provide early childhood education from morning to evening, serving children from six weeks to school age. They are essential for working parents, offering continuous care and supervision. Many daycare centers struggle to provide effective education and care, highlighting the need for better curriculum designs. The Montessori method, known for its child-centered approach, offers a potential solution.Aim : To analyze the implementation of the Montessori method in daycare services for children aged one to three years, focusing on curriculum design, execution, and evaluation.Method : This study uses a literature review method, gathering data from primary and secondary sources. Information was collected, organized, and analyzed to understand the effectiveness of the Montessori method in daycare settings.Result : The Montessori method emphasizes child-centered learning with teachers as observers and facilitators. Key principles include a prepared environment, direct and concrete learning, respect, observation, and mixed-age groups. For children aged one to three, the curriculum focuses on five areas: eye and hand coordination, music and movement, practical life activities, arts and crafts, and language. Continuous evaluation through observation and personalized reports supports holistic child development.Conclusion : The Montessori method is effective for daycare services for children aged one to three years. It promotes child development through a structured, child-centered approach, with teachers facilitating independent learning. Continuous evaluation helps in understanding and supporting each child's growth, making the Montessori method a valuable approach for early childhood development in daycare settings.